Effects of Sugars on in vitro Culture of Bauhinia purpurea L. - Singh, Belai Meeta (Nepal Journal of Science and Technology, 2015)
Bauhinia purpurea L. is a moderate sized tree with multipurpose value. It is distributed in sub-Himalayan tracts. Propagation of this plant was tested on different sugars, maltose, sucrose, glucose, galactose, lactose and fructoseeach with MS medium. Multiplication rate of plants were recorded after 8 weeks of culture. Sucrose produced 2.20 nodes and 10.05 mm shoot length the other sugars did not induce shoot length elongation and node developments. DOI: http://dx.doi.org/njst.v15i2.12113 Nepal Journal of Science and Technology Vol. 15, No.2 (2014) 47-50